Existence and uniqueness of solution to a parabolic-hyperbolic equation with multiplicative control and nonlocally boundary conditions - Kapustyan, V.; Pyshnograiev, I. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.9We consider a parabolic-hyperbolic equation with multiplicative control and nonlocal boundary conditions. By using the Riess biorthogonal basis, the problem is reduced to a sequence of one-dimensional problems with alternative representations of their solutions. Conditions guaranteeing the existence and uniqueness of  solution to the analyzed problem are established.